Rheological properties of self-compacting mortar made with magnetic water - Omid Bamshad; Mahdi Mahdikhani (مهندسی و مدیریت ساخت)
The use of concrete in construction projects is increasing day by day. Making concrete with different properties, compatible with the conditions of each project, is necessary and unavoidable. So far, researchers have conducted research on the characteristics of this type of concrete. However, the role of water consumption in the mixing and curing of this type of concrete has not been studied much. Also, in some countries, studies are being conducted on the use of magnetic water and its effect on concrete. The purpose of this article is to investigate the changes in the properties of self-compacting mortars in the fresh state, due to the use of magnetic water in the construction phase, and therefore small slump tests and small v-shaped funnels are used as important criteria using normal and processed waters. It has been done for 5, 10, 15 and 20 minutes. The results of the tests show that magnetic water improves the rheological properties of fresh mortar.